PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PT BINTANG KEMAKUMURAN CABANG HANKAM BEKASI - Shintya Nur Aini; Freddrick Tiagita P (Jurnal Ekonomi dan Industri, 2020)
Along with the changing times, company leadership must be able to bring the company to be more developed and able to compete in changing times. In this case, company leaders must find the right strategy to achieve the goals they have set. To achieve a goal requires effective and efficient employee performance. Several factors can improve employee performance through the work environment and work motivation. This research was conducted to determine whether there is an influence of work environment and work motivation on employee performance simultaneously or partially at PT Bintang Kemakmuran cabang Hankam-Bekasi. This research method was conducted with 42 respondents, data were collected using a questionnaire with a Likert scale. The test results showed that the work environment and work motivation simultaneously had a significant effect on employee performance. In addition, the work environment and work motivation partially also have a significant effect on employee performance.